2020
DOI: 10.1002/ange.202008624
|View full text |Cite
|
Sign up to set email alerts
|

Recoding the Cancer Epigenome by Intervening in Metabolism and Iron Homeostasis with Mitochondria‐Targeted Rhenium(I) Complexes

Abstract: The development and malignancy of cancer cells are closely related to the changes of the epigenome.I nt his work, am itochondria-targeted rhenium(I) complex (DFX-Re3), integrating the clinical iron chelating agent deferasirox (DFX), has been designed. By relocating iron to the mitochondria and changing the key metabolic species related to epigenetic modifications, DFX-Re3 can elevate the methylation levels of histone,D NA,a nd RNA. As ac onsequence, DFX-Re3 affects the events related to apoptosis,R NA polymera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…White Powder, mp 235 -236 °C; 1 (40), 449 (9), 447 (10), 359 (18), 357 (20), 216 (15), 215 (100), 214 (15), 213 (99), 183 (3.9), 181 (4), 158 (2.5), 156 (3), 155 (25), 143 (2), 134 (50), 117 (2), 107 (9), 76 (8)…”
Section: Nn'-di(4-bromophenyl)-4-hydroxycoumarin-3carboximidamide (L1)unclassified
See 1 more Smart Citation
“…White Powder, mp 235 -236 °C; 1 (40), 449 (9), 447 (10), 359 (18), 357 (20), 216 (15), 215 (100), 214 (15), 213 (99), 183 (3.9), 181 (4), 158 (2.5), 156 (3), 155 (25), 143 (2), 134 (50), 117 (2), 107 (9), 76 (8)…”
Section: Nn'-di(4-bromophenyl)-4-hydroxycoumarin-3carboximidamide (L1)unclassified
“…Metal complexes have been used for a considerable time as pharmaceutical agents, especially in the chemotherapy against cancer [1,2]. More recently, large interest has grown in the use of transition metal complexes [3,6].…”
Section: Introduction *mentioning
confidence: 99%
“…Mitochondrial damage and/or dysfunction leads to impairment of mitochondrial membrane potential (ΔΨ m ). 55,56 To this end, a fluorescent ΔΨ m indicator, namely, 5,5,6,6′-tetrachloro-1,1′,3,3′-tetraethyl-imidacarbocyanine iodide (JC-1) dye, in combination with flow cytometry was used to measure ΔΨ m in 1-treated HeLa cells. In the case of healthy and functional mitochondria with intact ΔΨ m , the JC-1 dye accumulates in mitochondria as aggregates and is emitted in the red channel, whereas in case of unhealthy mitochondria with depleted ΔΨ m , the JC-1 dye accumulates as monomers inside mitochondria and is emitted in the green channel.…”
Section: ■ Introductionmentioning
confidence: 99%
“…On a similar note, intervening iron homeostasis pathway can also facilitate or augment immunogenic cell death. 66 Recent studies with a rhenium complex conjugated to an iron chelator deferasirox 67 showed upregulation of CRT translocation in MDA-MB-231 triple negative breast cancer cells. This is indicative of ICD induction in vitro ; however, further experiments with similar complexes need to be carried out to confirm the rationale.…”
Section: Discussionmentioning
confidence: 99%